2013
DOI: 10.1177/0963662512472159
|View full text |Cite
|
Sign up to set email alerts
|

The role of genes in talking about overweight: An analysis of discourse on genetics, overweight and health risks in relation to nutrigenomics

Abstract: This study examines whether the assumptions embedded in nutrigenomics, especially the alleged relation between information about personal health risks and healthy behaviour, match how people account for the relation between food, health and genes in everyday life. We draw on discourse analysis to study accounts of overweight in six group interviews with people who are and who are not overweight. The results show potentially contradictory normative orientations towards behavioural explanations of (over)weight. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
(51 reference statements)
0
2
0
Order By: Relevance
“…Although this is more tangential to the precision nutrition landscape, searches used to seek information about nutrigenetics or omics will include information on this topic. It has also been suggested that discourse on the role of genetics and lifestyle in weight is an important precursor to understanding consumer responses to nutrigenetics [57]. More broadly, the role of genes in weight is a popular topic of public discussion, and weight loss is a major topic of conversation on Twitter [58].…”
Section: Tweets About Genetics and Body Weight Or Sizementioning
confidence: 99%
“…Although this is more tangential to the precision nutrition landscape, searches used to seek information about nutrigenetics or omics will include information on this topic. It has also been suggested that discourse on the role of genetics and lifestyle in weight is an important precursor to understanding consumer responses to nutrigenetics [57]. More broadly, the role of genes in weight is a popular topic of public discussion, and weight loss is a major topic of conversation on Twitter [58].…”
Section: Tweets About Genetics and Body Weight Or Sizementioning
confidence: 99%
“…Although discursive psychology has rarely been applied as a technology assessment tool, there are a few exceptions. For example, a study of people's talk about notions of health and risk that are central to nutrigenomics highlights the tension between the assumption that people will simply avoid unhealthy eating habits when informed about the health risks and the remarkable finding that people (have to) account for healthy behavior in their everyday interactions (Komduur & te Molder, 2011). In another study, analyses of celiac disease (CD) patients' interactions with other patients, family members, and experts are used to gain insight into patients' everyday-life practices on which innovations of Celiac Disease Consortium research will have an impact, with the aim of incorporating patients' concerns and wishes into the development trial (te Molder, Bovenhoff, Veen, te Molder, Gremmen, & Van Woerum, 2010.…”
Section: Discursive Psychologymentioning
confidence: 99%